2015
DOI: 10.1007/s00276-015-1513-9
|View full text |Cite
|
Sign up to set email alerts
|

Topography of inferior epigastric artery relevant to laparoscopy: a CT angiographic study

Abstract: The security distance for safe trocar placement was 6 cm at the level of ASIS and 9 cm at the level of umbilicus. Preoperative IEA assessment is helpful in reducing injuries to IEA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 10 publications
(14 reference statements)
0
9
0
1
Order By: Relevance
“…A number of studies have challenged the 8-cm boundary suggested by Saber et al [7]. A more recent CT imaging study suggested that a 9-cm margin at the umbilicus is necessary to avoid deep epigastric vessel injury [16]. Similarly, Epstein et al [5] examined cadavers and found the inferior epigastric artery as far lateral as 9 cm at the ASIS and 9.5 cm at the level of the umbilicus; however, the embalmed nature of the cadavers and advanced age raise concerns about generalizability to surgical patients.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…A number of studies have challenged the 8-cm boundary suggested by Saber et al [7]. A more recent CT imaging study suggested that a 9-cm margin at the umbilicus is necessary to avoid deep epigastric vessel injury [16]. Similarly, Epstein et al [5] examined cadavers and found the inferior epigastric artery as far lateral as 9 cm at the ASIS and 9.5 cm at the level of the umbilicus; however, the embalmed nature of the cadavers and advanced age raise concerns about generalizability to surgical patients.…”
Section: Discussionmentioning
confidence: 98%
“…Various studies have been completed to map the deep epigastric vessel location to avoid injury while placing laparoscopic accessory trocars [7,8,[12][13][14][15][16]. Although the distance from the midline varies somewhat among studies, the deep epigastric vessels were consistently found within 9 cm from the midline, above the level of the pubic symphysis (PS).…”
mentioning
confidence: 99%
“…There was a definitive predictive pattern in the course of the artery as seen in correlation and regression analysis. [6] Epstein et al . in their study of 30 cadavers (18 female and 12 male) found that the IEA ran vertically throughout its course in the anterior abdominal wall.…”
Section: Discussionmentioning
confidence: 99%
“…In man, the reported incidence of abdominal wall vessel injury during laparoscopic surgery is between 0.2% and 2% . Complications reported in human literature from abdominal wall vessel injury are similar to those in the veterinary literature, with the addition of necrosis of the rectus abdominis muscle, aortoiliac disease, and death . Abdominal wall vessel injuries in patients during laparoscopic procedures, paracentesis, and abdominal drain placement have led to numerous studies attempting to define the course, variations, and relation of body mass to the location of the epigastric vessels.…”
Section: Introductionmentioning
confidence: 92%
“…These studies determined the course of the epigastric vessels with cadaveric studies, computed tomography, and Doppler ultrasound. Current clinical methods for avoiding the abdominal vessels during laparoscopic portal placement in human surgery include the use of external anatomical landmarks, direct laparoscopic visualization, transillumination, computed tomography, and Doppler ultrasound …”
Section: Introductionmentioning
confidence: 99%